Protein, esterase and peroxidase patterns of phytophthora isolates from cocoa in Malaysia - Meon, Sariah (1988)
Protein, esterase and peroxidase patterns of eighteen isolates of P. palmivora from various cocoa growing areas of Peninsular Malaya, Sabah dan Sarawak were studied by polyacrylamide vertical gel electrophoresis, to determine whether "strain" within P. palmivora could be distinguished using this method. The protein patterns of all the isolates studied were almost identical qualitatively and it was impossible to distinguish "strain" between the isolates of P. polmivora from cocoa. Esterase and peroxidase patterns of the isolates were also identical, although the amount of enzyme varies as observed by variation of color intensity of the bands.